2018
DOI: 10.1371/journal.pone.0207657
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pulmonary complications following posterior spinal instrumentation and fusion for congenital scoliosis

Abstract: BackgroundCongenital scoliosis (CS) may lead to more serious pulmonary complications compared with idiopathic scoliosis after spinal fusion surgery. However, little has been reported about postoperative pulmonary complication events in patients with CS after spinal fusion surgery.ObjectiveTo investigate the incidence of and predictive factors of postoperative pulmonary complications following posterior spinal instrumentation and fusion surgery for the treatment of CS.MethodsWe retrospectively reviewed the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 25 publications
1
29
2
Order By: Relevance
“…[7][8][9][10] The cumulative incidence of pulmonary complications after spine surgery has ranged from 0.6% to 14.9%. 2,[7][8][9]11,12 The differences in incidence may be attributable to the variations in the definition of pulmonary events in the various studies, the underlying etiologies, and surgical complexities. 2,[7][8][9][10][11][12] Higher rates of pulmonary complication have been reported for neuromuscular patient populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] The cumulative incidence of pulmonary complications after spine surgery has ranged from 0.6% to 14.9%. 2,[7][8][9]11,12 The differences in incidence may be attributable to the variations in the definition of pulmonary events in the various studies, the underlying etiologies, and surgical complexities. 2,[7][8][9][10][11][12] Higher rates of pulmonary complication have been reported for neuromuscular patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…2,[7][8][9]11,12 The differences in incidence may be attributable to the variations in the definition of pulmonary events in the various studies, the underlying etiologies, and surgical complexities. 2,[7][8][9][10][11][12] Higher rates of pulmonary complication have been reported for neuromuscular patient populations. 10 The concern for pulmonary complications is even greater in underserved regions with limited expertise and resources.…”
Section: Introductionmentioning
confidence: 99%
“…However, little has been reported about postoperative pulmonary complication in CS patients. Yin et al recently investigated the pulmonary complication in CS patients, but the sample size of their study was small and the observation variables were inadequate [11]. Therefore, we conducted this retrospective study to describe the morbidity and further try to find the risk factors of postoperative pulmonary complications after posterior spinal instrumentation and fusion surgery in CS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some differences in these markers were identified, for example in our group the Cobb angle cut‐off was >90° whereas Kang et al 18 found a relationship with Cobb angle >69°, although all their patients had neuromuscular diseases. Recently, Yin et al 3 reported a cobb angle of >77° as a predicted factor for postoperative pulmonary complication. This difference in Cobb angle value could mainly be due to the fact that the majority of our subjects had Idiopathic scoliosis.…”
Section: Discussionmentioning
confidence: 99%